2013
DOI: 10.2528/pier13042408
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter Wave Subharmonic Mixer Implementation Using Graphene Film Coating

Abstract: In this work, a subharmonic frequency mixer for millimeter wave applications has been designed. The mixing and multiplication phenomena are simultaneously achieved via a nonlinear component consisting in a microstrip line gap covered by a graphene film coating. The circuit structure is made up of various filters, which have been optimized to ensure high port-to-port isolation. The nonlinear behavior of the subharmonic frequency mixer has been experimentally evaluated within the 39-40.5 GHz RF frequency band. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Moreover, the previously reported works have shown that the microscopic mechanisms that cause such effects in graphene are very different and strongly enhanced when compared with those observed in conventional semiconductors [2,14]. High-efficiency second-and third-harmonic generation effects have been achieved in monolayer graphene-based transistors, from relatively low frequencies up to the millimeter-wave frequency band [15][16][17], and they have also been experimentally observed in few-layer graphene sheets [6,8,11,13]. Therefore, such results can constitute the basis for the development of a radically new generation of electronic devices.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, the previously reported works have shown that the microscopic mechanisms that cause such effects in graphene are very different and strongly enhanced when compared with those observed in conventional semiconductors [2,14]. High-efficiency second-and third-harmonic generation effects have been achieved in monolayer graphene-based transistors, from relatively low frequencies up to the millimeter-wave frequency band [15][16][17], and they have also been experimentally observed in few-layer graphene sheets [6,8,11,13]. Therefore, such results can constitute the basis for the development of a radically new generation of electronic devices.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, a great number of nonlinear phenomena, including second [3][4][5][6][7]-and third [8][9][10]-harmonic generation and frequency mixing [11][12][13], have also been theoretically predicted and experimentally demonstrated. Moreover, the previously reported works have shown that the microscopic mechanisms that cause such effects in graphene are very different and strongly enhanced when compared with those observed in conventional semiconductors [2,14].…”
Section: Introductionmentioning
confidence: 98%
“…122 Due to the rapid development in technology, circuits at millimeter and submillimeter frequencies are becoming the great challenges for conventional mixers, which require higher data rate transmissions. 123 As a typical 2D atomic crystals, graphene has been considered as a potential material for high-frequency mixers, especially at millimeter and submillimeter waves, due to its high intrinsic carrier mobility and high carrier saturation velocity. [124][125][126] Lin et al reported a graphene mixer integrated with a graphene FET and a pair of inductors on a single silicon carbide wafer, demonstrating a broadband radio-frequency mixer at frequencies up to 10 GHz and excellent thermal stability up to 125°C.…”
Section: Mixer Switch Modulator and Resonatormentioning
confidence: 99%
“…The graphene film integrated in the microstrip structure is prepared by mechanical exfoliation of Highly Oriented Pyrolytic Graphite (HOPG) [24]- [26], [28]. Metallic contacts, as depicted in Fig.…”
Section: Multiplier Topologymentioning
confidence: 99%